Long-term storage, cryopreservation, and culture of isolated human islets: a systematic review - Chen, Austin R.; Chansky, Joshua; Burke, Jacqueline A. (Frontiers in Transplantation, 2025)
IntroductionIslet transplantation offers a potential curative treatment for patients with type 1 diabetes (T1D). To make this therapy widely available, a stable supply chain of human islets is essential. Developing techniques like cryopreservation and culture for long-term islet storage, or islet banking, with minimal functional loss would strengthen this supply chain. This study provides a systematic review of the current methods for long-term human islet storage.MethodsA search strategy and query were developed according to the PICO framework. We included studies published on PubMed, Embase, and Web of Science from inception until August 2024.Results6,945 studies were screened with 47 meeting criteria for full text extraction. The primary outcomes recorded were measures of islet viability and glucose stimulated insulin secretion. Optimization of culture parameters such as temperature, medium selection, and scaffolds can extend islet viability and function.DiscussionRecent studies on human islet cryopreservation report promising results for long-term storage; however, the field remains underexplored. Several cytoprotective supplements with potential utility across both culture and cryopreservation conditions have also been reviewed. Although long-term islet storage has been a critical focus since the advent of the Edmonton protocol, the literature lacks the rigor needed to drive clinical translation. Notably, we observe substantial variability in experimental design and reported outcomes, which complicates meaningful comparison between interventions.